Nonanuclear Ni(ii) complexes in a [1-7-1] formation derived from asymmetric multidentate ligands: magnetic and electrochemical properties. Issue 12 (9th February 2018) - Tsuji, Yasuhiro; Togo, Tatsuo; Mishima, Akio; Koshiyama, Tomomi; Ohba, Masaaki
Abstract : Asymmetric multidentate ligands H2 L n formed unique nonanuclear Ni(ii ) complexes, [Ni9 (L n )6 (OH)6 (H2 O)6 ] via self-assembly. A corner-sharing tetrahedron-type structure, [Ni7 (μ3 -OH)6 ] 8+, and terminal mononuclear units constitute the nonanuclear structure in a [1-7-1] formation. Abstract : Nonanuclear Ni(ii ) complexes, [Ni9 (L n )6 (OH)6 (H2 O)6 ] (Ni9 L n, n = 1–4; H2 L n = 6-acetoacetyl-2-pyridinecarboxylic acid derivatives), were prepared via self-assembly using the asymmetric multidentate ligands H2 L n . A corner-sharing tetrahedron-type structure, [Ni7 (μ3 -OH)6 ] 8+, and terminal mononuclear units constitute the nonanuclear structure in a [1-7-1] formation. The electrochemical and magnetic properties of Ni9 L n were modulated by the introduction of various substituents in H2 L n .